Effects of Structural Adjustment Programs on Saving, Investment and Growth: A Case Study of Sudan - Hassan, Ahlam Abd Elhadi (2003)
Sudan economy has experienced a prolonged period of internal and external imbalances. Inappropriate policies have caused misallocation of resources and the lowering of productivity and employment. Macroeconomic instability placed further strain on growth by reducing investors' confidence in the economy. To cope with the situation, Sudan, by the end of fiscal year 1978, has resorted to international borrowing which ushered in the Structural Adjustment Programs (and stabilization): the reform measures required by the International Monetary Fund and the World Bank as a condition for their loans. The Structural Adjustment Program is an economy-wide, all embracing, and comprehensive set of policy reforms aimed at expanding and strengthening the role of the market forces for efficient allocation of resources. The main objective of the study is to examine the effects of the Structural Adjustment Programs on the Sudanese economy. In particular, the study analyzes interactions between structural reform and selected macroeconomic variables including saving, investment and growth. Annual data covering the period 1955 to 1998 was used. A six-equation model with six variables was used in the study. A dummy variable was included as an exogenous variable to capture the effects of a Comprehensive Strategy Structural Program. which was implemented in Sudan. The results of this study indicate that there was a positive correlation between growth, investment, and savings and show the important role of structural reform in determining all three variables. The structural programs in the Sudanese economy had positive effects on saving and investment, but its impact on the growth rate was negative in the short run. The findings tend to confirm the predominant view that sound macroeconomic policies and structural reforms are crucial for saving, investment and growth. To improve the productivity of investment, the Sudanese government should identify and undertake investments that have positive net returns. Increased emphasis on education and the adoption or maintenance of outward oriented policies, for example removal of export taxes, and improvement in investment policies, in all fronts, are needed. These are capable of stimulating investment and spurring sustainable long-term economic growth. Coordination and better targeting of foreign assistance resources on specific projects that can create the conditions for trade and saving, are required; knowing that foreign assistance can be used strategically to foster reforms.